Formulation development for cancer compounds – Biopharmaceutical issues and perspectives - Srinivas, Nuggehally R (Asian Journal of Pharmaceutics (AJP), 2014)
The development of formulations for anti-cancer drugs imposes challenges owing to the different physicochemical attributes of the compounds as well as the need to deliver the compound to the desired target and/or tumor sites. In this article we present case studies to discuss recent formulation related work for both paclitaxel and topotecan. As enumerated by the case studies, biopharmaceutical and pharmacokinetic challenges are imposed in design and optimization of suitable dosage forms for both intravenous and oral drug delivery. The focus is on selection of excipients which may play additional role(s) in contributing towards the disposition of both paclitaxel and topotecan.